Challenges in Parole Supervision: Views from the Field. Issue 4 (1st October 2016) - Vîlcică, E. Rely
ABSTRACT: This article looks at parole supervision from the perspective of those most directly tasked with it, the parole field officers. The article draws on qualitative data (a focus group with parole officers) from one large state (Pennsylvania), collected as part of a larger inquiry following the imposition of a moratorium on all parole releases, which was triggered by a series of violent incidents involving recently released parolees. The special circumstances of the research allowed an in-depth investigation of the state's parole processes. The perspectives of the parole field officers, discussed here, are particularly illumining about the challenges encountered in the day-to-day task of supervising parolees. The policy implications that emerged from considering the views of parole officers are also discussed.